Kinetic and Isothermal Investigations of Cost-Effective Sorptive Elimination of Gentian Violet Dye from Water Using Haplophragma adenophyllum Biowaste - Momal Akram; Muhammad Salman; Rabia Rehman; Umar Farooq; Samra Tahir; Huma Nazir (Journal of Chemistry)
A novel biosorbent, Haplophragma adenophyllum (HAB) was employed to explore the biosorption mechanism of Gentian Violet (GV) dye. The novel sorbent was characterized by using FTIR spectra and physiochemical analysis. The effect of different optimizing factors like HAB dosage, GV initial concentration, contact time between sorbent and sorbate, pH of a solution, and the temperature was studied. The optimum removal of GV by HAB was observed at pH 6.0. The equilibrium study was carried out using Langmuir and Freundlich isotherms. Experimental data fitted well in Langmuir isotherm indicating monolayer isotherm with qmax value obtained at optimum process condition of 13.21 mg/g. Kinetics study was carried out and followed by pseudo-second-order model. Thermodynamics studies reveal the endothermic reaction.